Benford's Law for Quality Assurance of Manner of Death Counts in Small and Large Databases. Issue 5 (20th June 2017) - Daniels, Jeremy; Caetano, Samantha‐Jo; Huyer, Dirk; Stephen, Andrew; Fernandes, John; Lytwyn, Alice; Hoppe, Fred M.
Abstract: To assess if Benford's law, a mathematical law used for quality assurance in accounting, can be applied as a quality assurance measure for the manner of death determination. We examined a regional forensic pathology service's monthly manner of death counts ( N = 2352) from 2011 to 2013, and provincial monthly and weekly death counts from 2009 to 2013 ( N = 81, 831). We tested whether each dataset's leading digit followed Benford's law via the chi‐square test. For each database, we assessed whether number 1 was the most common leading digit. The manner of death counts first digit followed Benford's law in all the three datasets. Two of the three datasets had 1 as the most frequent leading digit. The manner of death data in this study showed qualities consistent with Benford's law. The law has potential as a quality assurance metric in the manner of death determination for both small and large databases.